Assessing Political Risk Analysis in a hybrid regime: The case of Zimbabwe (The Strategic Review for Southern Africa, 2021)
Political Risk Analysis (PRA) levels are theoretically postulated to increase in a hybrid regime. This paper argues that there is a change to this hypothesis. A single case research design was employed, using Zimbabwe from 1990 to 2018. During the period, Zimbabwe showed five diverse forms of hybridity which are liberal, competitive illiberal, competitive, illiberal, and military hybrid regimes. A conceptual framework is developed to assess political risk in a hybrid regime using hybrid regime indicators and some political risk factors of most concern to developing countries. 28 key informants from six categories of respondents were interviewed. Illegitimacy, corruption, the staleness of leadership, adverse government regulation, election violence, and severed home-host state relations were confirmed to increase the perception of political risk in a hybrid regime. Investors were observed to have developed a tolerance for some “unacceptable” factors that increased political risk. Military tutelage, weak institutions, flawed elections, military generals in power, undemocratic means to retain power, minimum horizontal accountability and weak rule of law were found to not automatically increase political risk as before. The paper concludes that there is no single form of hybridity and as such different forms of hybrid regimes accrue different levels of political risk, some lower levels while others substantially higher levels. Therefore, in a hybrid regime, a differentiated PRA monitoring, assessing and mitigation strategy will be most effective for management to implement. Future studies can apply the analytical framework of assessing PRA in a hybrid to another hybrid regime to expand the theoretical propositions made by this paper.
Keywords: Political Risk Analysis, Political risk, Hybrid regime, Risk assessment and mitigation